1980
DOI: 10.1073/pnas.77.7.3758
|View full text |Cite
|
Sign up to set email alerts
|

Field-induced trapping as a probe of dimensionality in molecular crystals

Abstract: The combined effect of an electric field and reduced dimensionality on the hopping motion of a charge carrier in. an anisotropic molecular crystal is determined.'New, exnct -expressions for S(t), the number of distinct sites occupied by a carrier'in time t, are presented for two-dimensional and iree-dimensional anisotropic lattices. The general results are used to model the unusual phenomenon of field-induced charge carrier trapping reported to occur in a quasi-one-dimensional moleculan crystal. An analytic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…It can be evaluated by expanding the molecular field and field response in terms of distributed multipoles and polarizabilities. Only a few studies have discussed the influence of this perturbation on the transport behavior of P3HT: systems of up 10 4 thiophenes have been treated in this fashion, for example, in order to explore the density of states of P3HT in dependence on polymorph and regioregularity or at interfaces …”
Section: Theoretical Studies Of Hole Transport In P3ht and P3ht:pcbm supporting
confidence: 68%
See 1 more Smart Citation
“…It can be evaluated by expanding the molecular field and field response in terms of distributed multipoles and polarizabilities. Only a few studies have discussed the influence of this perturbation on the transport behavior of P3HT: systems of up 10 4 thiophenes have been treated in this fashion, for example, in order to explore the density of states of P3HT in dependence on polymorph and regioregularity or at interfaces …”
Section: Theoretical Studies Of Hole Transport In P3ht and P3ht:pcbm supporting
confidence: 68%
“…Side‐chain melting leads to a broadening of the distributions and a tail of very small couplings, down to 10 −6 eV (even though only nearest neighbors are present in the neighbor list). This would obviously result in rather small average mobility values . However, this conclusion is valid only if (one‐dimensional) charge‐carrier transport were to occur within a static snapshot of the system.…”
Section: Theoretical Studies Of Hole Transport In P3ht and P3ht:pcbm mentioning
confidence: 99%
“…This would obviously result in rather small average mobility values. 79 However, this conclusion is valid only if (onedimensional) charge-carrier transport were to occur within a static snapshot of the system; in reality, both transfer integrals and site energies are time-dependent. In order to understand whether such a static picture can be used in our case, we evaluate the distributions of relaxation times of the electronic coupling elements and energies and compare them to the distribution of escape times of a charge carrier in section IVC.…”
Section: Charge Transportmentioning
confidence: 99%
“…Conjugated polymers are an interesting case, both because of their high technological relevance and their inherent transport anisotropy due to their single covalently linked p-electron dimension. [126] One-dimensional diffusive transport is more rapid than higher dimensional diffusive transport, [127] which can be an advantage in applications where the short lifetime of the singlet exciton is a limitation. Barbaras group showed that an indirect consequence of charging a polymer is the formation of an exciton cascade.…”
Section: Exciton Motionmentioning
confidence: 99%